Strategies for extreme self-organization among handball players - Plokhikh, V.; Popovych, I.; Kruglov, K.; Sabadukha, O.; Melnyk, N.; Omelianiuk, S.; Hoian, I. (Journal of Physical Education and Sport, 2024)
Aim This study aims to conduct theoretical and empirical research into the strategies of extreme self- organization among handball players in competitive context.